Comparative Competence of Science Educators on the New Licensure Examination as Basis for a Review Program - Camara, Jun S. (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
The demand to prepare future science educators for national board examinations necessitates teacher training institutions to assess the licensure competence of pre-service teachers. In the case of the Philippines, the Licensure Examination for Teachers or LEPT has new competencies, which have not been fully assessed on the perspective of pre-service teachers. In this, the researcher assessed and compared the self-reported competence of alumni (a, n=38) and ongoing pre-service teachers (o, n=43) of a large state university in the Philippines. To do this, the researcher developed a survey-questionnaire with contents based on the Enhanced Table of Specifications or TOS for LEPT which was first implemented in March 2023 in the Philippines, the survey was conducted during the 1st semester of S.Y. 2023-2023. Results revealed that the pre-service teachers (n=81) have high level of competence for the LEPT. Further, the level of competence of alumni is comparable to those of on-going students. However, a significant difference was found in competencies related to Challenging Activities in Science, Assessment Tools, Basic Biotechniques, and Waves and Optics, where alumni demonstrated a significantly higher competence. To provide continuity for the findings, the researcher proposes a review program for Filipino pre-service teachers based on the findings. Furthermore, the researcher recommends that a content-competency alignment will be conducted between the Enhanced TOS of LEPT and the latest relevant issuances on Policies, Standards and Guidelines (PSGs) for Education degree programs issued by the Commission on Higher Education. Moreover, a curriculum mapping is recommended between the Enhanced TOS and the MATATAG Curriculum for Science. To provide an international perspective, the researcher recommends an analysis of licensure competencies for teachers among ASEAN countries.